Study on the application of green energy in a mini-AC cooling system utilizing peltiermodule and heat pipe technology - Irwin Bizzy; Darmawi Darmawi; Agung Mataram; Fadhil Fuad Rachman (Jurnal Polimesin, 2024)
The climate in tropical countries is very humid and hot, so it requires cooling and regulating air humidity. Heat release from the heat side using a heat sink, such as the conventional Peltier method, does not function optimally due to the limited area of thermal resistance obtained. To increase the thermal resistance in heat release, a heat pipe is used as a passive heat exchange device so that it can maximize heat transfer from the hot side of the Peltier to the surrounding air. This research aims to determine the rate of heat transfer, whether it can be conditioned by the relative humidity (RH) in the room, and whether installing a temperature and RH control system can work to cool the room. Experimental methods were used in this research. This research results show that TEC Cooler can transfer heat to a maximum. TEC can transfer heat at 22.7 J/s per second with 3 running fans. With a power consumption of 136.1 W. The total energy released is 114.7 J/s; this energy is still considered suitable for use in cooling a room.